Analisis Kebutuhan pada Perancangan Antarmuka Pengguna Aplikasi Koperasi Menggunakan Design Thinking - Nur'aeni, Fina; Fathoni Mahardika; Dani Indra Junaedi; Agun Guntara (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The development of information technology encourages cooperatives to adapt to digital systems to improve efficiency, transparency, and accuracy in managing membership and financial data. This study aims to analyze user needs as the basis for designing a user interface for a cooperative membership and financial management application using the Design Thinking method. This method consists of five stages: empathize, define, ideate, prototype, and test. The study focused on needs analysis with the initial stages: empathize, define, and ideate. The empathize stage involved interviews with cooperative administrators and members, followed by identification through the define stage. The analysis results indicated that users require an efficient, secure, and transparent digital system with key features such as member registration, online payments, bill notifications, and automated financial reports. The ideate stage resulted in a design idea that comprehensively describes user needs. This allows for a design that adapts to the analysis results. Thus, the Design Thinking approach has proven effective in understanding user problems and needs and provides a strong foundation for designing a cooperative application interface that is user-friendly and appropriate to the organization's operational context.